Seasonal and environmental effects on breast milk fatty acids in Burkina Faso and the need to improve the omega 3 PUFA content - Thiombiano-Coulibaly, N; Rocquelin, G; Eymard-Duvernay, S; Kiffer-Nunes, J; Tapsoba, S; Traoré, SA (Acta Paediatrica, 2003)
Aim: To determine the Burkinabè breast milk lipid content and fatty acid composition and to compare these values with the recommended adequate intakes. Methods: The study comprised four cross‐sectional surveys conducted in urban and rural Burkina Faso at two different times of the year: during a period of food shortage (lean season) and during a favourable food availability period (post‐harvest season). The subjects were apparently healthy mothers nursing 5‐mo‐old infants. A total of 70 urban and 52 rural mothers and 100 urban and 98 rural mothers, respectively, during the post‐harvest season and the lean season, completed the surveys. The surveys were conducted in January‐February 2001 (urban) and 2002 (rural) corresponding to the post‐harvest season, and in April‐May 1998 (urban) and 1999 (rural), which is the lean season, and were carried out during home visits. The families were informed of the objectives of the study and gave their consent to participate. Breast milk samples were collected from each mother and analysed for lipid and fatty acid concentrations. Results: Noticeable breast milk characteristics were: low lipid content (30‐35 g/L), high C6:0‐C14:0 saturated fatty acids (27%‐33% total fatty acids), high linoleic acid (15%‐20% total fatty acids) and unbalanced linoleic/α‐linolenic acid (20:1 to 53:1) and long‐chain ω6/long‐chain ω3 (3.6:1 to 4.9:1) polyunsaturated fatty acid ratios. In all life conditions and food availability, linoleic acid was in excess of and α‐linolenic was below the recommended adequate intakes. Over 80% of breast milk samples had linoleic/α‐linolenic acid and long‐chain ω6/ω3 polyunsaturated ratios well above the recommendations. Conclusion: Improvement in breast milk ω3 PUFA seems to be recommendable in Burkina Faso, where breastfeeding is the primary infant feeding practice.